Optimization of recombinant Zika virus NS1 protein secretion from HEK293 cells - Roldan, Julieta Suyay (2020)
Sensitive, accurate and cost-effective diagnostic tests are urgently needed to detect Zika virus (ZIKV) infection. Nonstructural 1 (NS1) glycoprotein is an excellent diagnostic marker since it is released in a hexameric conformation from infected cells into the patient's bloodstream early in the course of the infection. We established a stable rZNS1-His-expression system in HEK293 cells through lentiviral transduction. A novel optimization approach to enhance rZNS1-His protein secretion in the mammalian expression system was accomplished through 50 nM rapamycin incubation followed by serum-free media incubation for 9 days, reaching protein yields of ∼10 mg/l of culture medium. Purified rZNS1-His hexamer was recognized by anti-NS1 antibodies in ZIKV patient's serum, and showed the ability to induce a humoral response in immunized mice. The obtained recombinant protein is a reliable biological tool that can potentially be applied in the development of diagnostic tests to detect ZIKV in infected patients during the acute phase.